Media, politics and state broadcasting in Greece. (August 2019) - Iosifidis, Petros; Papathanassopoulos, Stylianos
This article focuses on governmental control over state broadcasting media in Greece and analyses whether Hellenic Broadcasting Corporation can be considered as public or state broadcaster. The first part explores the interrelationship between media, politics and the state in Greece, and the ways the latter has affected the development of Hellenic Broadcasting Corporation. By doing so, it makes references to similar Southern European broadcasting models that are also characterised by clientist manners, ministerial censorship, a powerful state and a weak civil society. Furthermore, it looks at the devastating impact of haphazard deregulation and market liberalisation on Hellenic Broadcasting Corporation since the early 1990s, when the Hellenic Broadcasting Corporation lost much of its formerly loyal audience and advertising income to a number of newly launched commercial television channels. Part 2 assesses the degree of political, editorial and financial independence of Hellenic Broadcasting Corporation under the current SYRIZA-led administration. Hellenic Broadcasting Corporation was re-launched by the left-wing SYRIZA government after a temporary 2-year closure, but it is struggling to maintain a competitive advantage and a politically neutral output.